Comparison of the Clinical Accuracy Between Point-to-Point Registration and Auto-Registration Using an Active Infrared Navigation System. Issue 22 (15th November 2018) - Zhao, Jingwei; Liu, Yajun; Fan, Mingxing; Liu, Bo; He, Da; Tian, Wei
Abstract : Study Design: A model experiment. Objective: To measure and compare the clinical accuracy of point-to-point registration (PR) and auto-registration (AR) in an operative set using an active infrared navigation system. Summary of Background Data: PR and AR are two major registration methods of navigation assisted spinal surgery. No previous study compared the difference between the two methods with respect to clinical accuracy. Methods: A novel method was used to measure the clinical accuracy of the navigation system under an operative set using a Sawbone model with titanium beads on the surface, which was essential to measure the accuracy numerically, instead of a real patient. Both the operative set and the procedure mimicked a regular surgery. The clinical accuracy was defined as the average distance between the "navigation coordinate" and the "image coordinate." The clinical accuracy of the PR using preoperative computed tomography (CT) images and the AR using intraoperative CT images was measured and compared. Results: The average clinical accuracy of PR was different among different segments. The accuracy of the most accurate segment, which provided the reference points during the PR, was 1.10 mm. In the two segments adjacent to the reference segment, the clinical accuracy deteriorated to 1.37 and 1.50 mm. The accuracy of the farther segments was worse. In comparison, the clinical accuracy of different segments of AR was of no significant difference. The average accuracy of AR was 0.74 mm, which was significantly better than the best accuracy of PR. Conclusion: AR is better than PR with respect to clinical accuracy in navigation assisted spinal surgery. Level of Evidence: N/A